CODE SWITCHING FOUND IN SUKA DAMAI PLAY GROUP OF KOTAKEO - Wea, Yulianus W W; Sama, Gratiana; Doi, Maksimilianus (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2022)
This research aimed at finding out the types and influencing factors of Code Switching in Bilingual Children Found in Suka Damai Play Group of Kotakeo. It was conducted in Kotakeo village, Nangaroro sub-district of Nagekeo regency. This study used descriptive qualitative method in analyzing the Code Switching Found in suka Damai Play Group. The theory of Wardaugh (2002) was used to discuss the types of code switching and the Holmes’ theory (2001) used to discuss the influencing factors. The result of this study indicates that were two types of code switching: situational code switching and intra-sentential code switching. The influencing factors of code switching were status and topic. The uniqueness of this research were found one of the two types of code switching which very dominant was situational code switching that influenced by topic in bilingual children found in Suka Damai Play Group of Kotakeo.